2022
DOI: 10.1007/s00704-022-04032-5
|View full text |Cite
|
Sign up to set email alerts
|

Spatio-temporal variability of lightning climatology and its association with thunderstorm indices over India

Abstract: Lightning is an electrical discharge -a'spark' or 'flash' as charged regions in the atmosphere instantly balance themselves through this discharge. It is a beautiful and deadly naturally occurring phenomenon. In June 2020, more than a hundred people died in the state Bihar of India only in three days' span due to lightning events. In this work, Lightning Imaging Sensor (LIS) information from the Tropical Rainfall Measuring Mission (TRMM) satellite with a very high spatial resolution of 0.1 X 0.1 degree has bee… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 26 publications
(14 citation statements)
references
References 63 publications
0
14
0
Order By: Relevance
“…1). A similar study was done by Mondal et al (2022), examining the hotspots region in India with the highest ash rate density that will help provide early warning and arrangements for the safety of the people, livestock, and property.…”
Section: Introductionmentioning
confidence: 92%
“…1). A similar study was done by Mondal et al (2022), examining the hotspots region in India with the highest ash rate density that will help provide early warning and arrangements for the safety of the people, livestock, and property.…”
Section: Introductionmentioning
confidence: 92%
“…Reviewing several articles, I found that many researchers have employed different machine learning methods. It also highlights the importance of machine learning in forecasting outcomes [5]. Various machine learning models have been developed to forecast thunderstorms: Linear Regression, Decision Tree, Support Vector Machine, etc.…”
Section: Machine Learningmentioning
confidence: 99%
“…As per the record around nine percent of the death due to natural hazard is caused by the lightning in India (Siingh et al, 2014;Yadava et al, 2020). The highest number of thunderstorms occur in the pre-monsoon months of (March, April, May, and early June) (Albrecht et al, 2016;Das, 2017;Mondal et al, 2022;Saha et al, 2017). The intensity of the thunderstorms are severe (Hoddinott, 1986) over India due to the topography (Barthlott et al, 2006;Mushtaq et al, 2018).…”
Section: Introductionmentioning
confidence: 99%